The Relation Between Levels of Parasitemia and the Anemia Condition in Domestic Cat (Felis catus) Infected with Trypanosoma evansi - Yusrivanda, Fesly Diva; Firdausy, Lintang Winantya; Priyowidodo, Dwi (Jurnal Sain Veteriner, 2025)
Trypanosoma evansi is a cause of the disease trypanosomiasis also known as surra. The trypomastigote stage can be found in the bloodstream and one of the clinical signs that appear during the course of the disease is anemia. The transmission of Trypanosoma evansi occurs non-cyclically through mechanical vector flies or oral transmission. This research aims to determine the relation between parasitemia levels and anemic conditions in domestic cats infected with Trypanosoma evansi. The objects used in this research are four domestic cats and divided into two groups based on the route of infection. The first group were infected with 108 Trypanosoma/µl (1 ml blood of an infected mice and PBS) through the subcutaneous route, and the second group was infected through the oral route by mixing carcass of infected mice and wet food. The examination of parasitemia levels in the blood samples of cats was observed daily using wet blood smear method and the hematological examination was collected within 10 days intervals during the experiment. The data of parasitemia levels and anemic condition in both groups were performed with descriptively and statistically analysis by using Independent T-test method. This research revealed that there was no significant effect (P>0.05) in anemia conditions between infection through subcutaneous and oral routes, and the level of parasitemia in the blood of domestic cats infected with Trypanosoma evansi affects the anemia condition, characterized by a decrease in the total value of erythrocyte, haemoglobin, and hematocrit.